Effect of Oxidative Stress on Estrus Synchronization and Pregnancy Rate after In-Vitro Produced Embryo Transfer in HF Crossbred Cattle - S Waghmare, Siddhesh; R Shelar, Raju; P Khillare, Kavita; N Rangnekar, Mahesh; B Mali, Ajit; N Jadhav, Sameer; B Jawane4, Vishnu (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present research involved 60 normal cycling recipients, including 30 heifers and 30 cows, synchronized using a double PGF2α protocol. A total of 140 oocytes were collected from 11 elite donors, averaging 12.72 oocytes per ovum pick-up (OPU) session at the Government Bovine Breeding Farm in Tathwade. Total 46 blastocyst-stage developed embryos were transferred to various farms in Western Maharashtra. Estrus response and ovarian corpora lutea (CL) development was higher in synchronized heifers (86.66%) than in cows (83.33%). Pregnant heifers had larger CL diameters and luteal areas than non-pregnant ones, while CL diameters in cows were similar regardless of pregnancy status. Total 24 (80.00%) heifers and 22 (73.33%) cows were suitable for embryo transfer. Overall, 76.66% of recipients received in-vitro-produced embryos, with conception rates of 50.00% in heifers and 31.82% in cows, resulting in an overall rate of 41.30%. Malondialdehyde (MDA) levels were higher in non-pregnant recipients compared to pregnant ones, suggesting that elevated MDA levels may be a useful selection criterion in embryo transfer technology.